RETRACTED: Production business operation planning of a wood processing plant - Sereda T.G.; Kostarev S.N.; Kochinov Y.A.; Kochinova T.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001